Thermal Treatment of Biomass: A Bibliometric Analysis—The Torrefaction Case - Knapczyk, Adrian; Francik, Sławomir; Jewiarz, Marcin; Zawiślak, Agnieszka; Francik, Renata (Energies (Basel), 2021)
The aim of the paper was to summarize and discuss current research trends in biomass thermal treatment (torrefaction process). Quantitative analyses were carried out, in which the main countries, research units and scientists were indicated. The analysis showed a clear upward trend in number of publications after 2010. Most scientists on selected topics come from China, USA, Canada, South Korea, Republic of China, Poland (Web od Science—Core Collection (WoS-CC) and Scopus databases). Quantitative analysis also showed that the most relevant WoS-CC categories in the summary are: Energy Fuels, Engineering Chemical, Agricultural Engineering, Biotechnology Applied Microbiology and Thermodynamics and Scopus Subject area: Energy, Chemical Engineering, Environmental Science, Engineering and Chemistry. Thematic analysis included research topics, process parameters and raw materials used. Thematic groups were separated: torrefaction process (temp.: 150–400 °C), hydrothermal carbonization process (HTC) (temp: 120–500 °C), pyrolysis process (temp.: 200–650 °C) and gasification and co-combustion process (temp.: 350–1600 °C). In the years 2015–2019, current research topics were: new torrefaction technologies (e.g., HTC), improvement of the physico-mechanical, chemical and energetic properties of produced fuel as well as the use of torrefied biomass in the process of pyrolysis, gasification and co-combustion. The raw materials used in all types of biomass thermal treatment were: energy crops, wood from fast-growing and exotic trees, waste from the agri-food industry, sewage sludge and microalgae.